Studi Bioekologi Betta fusca di Labuhanbatu Raya Sebagai Bahan Ajar untuk Mata Kuliah Ekologi Hewan - Risda Kesuma Lubis; Khairul Khairul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the bioecological aspects of Betta fusca as teaching material for the Ecology Course. The research method used is an exploratory method. The research results showed that the length-weight relationship of Betta fusca fish showed negative allometric results, which means that the increase in length of the fish was not proportional to the increase in weight. The male to female sex ratio was found to be 1:2, indicating the predominance of females over males in the observed population. The physical and chemical parameters of the water observed showed variations, but everything was still in optimum conditions to support the life of Betta fusca. The conclusion of this research is that the bioecological conditions of Betta fusca in Labuhanbatu Raya Regency still support the sustainability of the population of this species. Keywords: Betta fusca, Bioecology, Animal Ecology